Harmonizinng Knowledge Integration: Insights from Amin Abdullah and Nidhal Guessom in Pesantren-Based Higher Education - Agung Ilham Prastowo; Toto Suharto; Sembodo Ardi Widodo (AL-ISHLAH: Jurnal Pendidikan, 2023)
This article aims to find a feasible concept of integrated knowledge for pesantren-based higher education. This research is essential considering the issue of the integration of knowledge is still challenging for most educational institutions in Indonesia, especially higher education and pesantren. Higher education emphasizes the importance of general science based on research and methodology. it is important to adopt pesantren that emphasize Islamic teachings and building character. This research is based on a literature study where the data is taken from documents such as books, journals, and papers. The data analysis steps in this research are reducing data, presenting or displaying data, and verifying data or conclusions. The theistic science of Guessoum and the integration interconnection of Abdullah’s approach potentially solve this problem hence a comprehensive study on these theories is required. The outcome is the concept of integrated knowledge namely the integration of theistic science. It offers the development of general science based on the Divinity modern sciences. The integration of theistic science implemented in pesantren-based higher education should involve the aspects of philosophical foundation, the scope of integration, and educational goals.